Postpartum depression-associated localized neural dysfunction: a voxel-wise meta-analysis of amplitude and synchronization alterations in resting-state fMRI - Qiu, Jingjing; Wang, Hongjin; Zhao, Yu; Lin, Shen; Chen, Shangjie (Frontiers in Psychiatry, 2025)
BackgroundResting-state fMRI studies in postpartum depression (PPD) have reported voxel-wise alterations in measures of neural amplitude and synchronization, yet scarce meta-analysis has quantitatively synthesized these findings. We performed a coordinate-based meta-analysis to identify convergent amplitude and synchronization dysfunction in PPD.MethodsWe conducted a comprehensive search for whole-brain voxel-wise resting-state fMRI studies comparing PPD patients with healthy postpartum controls that reported local amplitude or synchronization metrics. Peak coordinates were analyzed using the Anisotropic effect size-signed differential mapping to delineate whole-brain functional alterations.ResultsTen studies (288 PPD patients, 279 controls) contributed 62 peak foci. Our analysis revealed that PPD patients exhibited increased activity in the left fusiform gyrus (FFG.L), left middle occipital gyrus (MOG.L), while showing decreased activity in the left anterior cingulate gyrus (ACG.L), the right superior temporal gyrus (STG.R), the right insula (INS.R) and the right precentral gyrus (PreCG.R) compared to healthy subjects. Jackknife sensitivity analysis indicated minimal impact on the overall results when eliminating any single study. Meta-regression analysis revealed a correlation between MOG.L functional activity and Edinburgh postnatal depression scale scores.ConclusionAbnormally elevated functional activity in the FFG.L, MOG.L, along with reduced activity in the ACG.L, STG.R, INS.R and PreCG.R, may serve as potential biomarkers for PPD. Additionally, abnormal functional activity in the visual cortex, and the prefrontal cortex-limbic system may be associated with PPD.